Complete Genome Sequence of Mycobacteriophage Fulbright - Kotturi, Hari (Microbiol Resour Announc, 2021)
Mycobacteriophage Fulbright was isolated from soil in central Oklahoma using Mycobacterium smegmatis mc(2)115. The genome of phage Fulbright is 42,396 bp long and contains 70 open reading frames (ORFs), with 33 having predicted functions and 37 having hypothetical proteins. It belongs to cluster N and shares 99% nucleotide identity with mycobacteriophage Phloss.